Implementasi Manajemen Mutu Pendidikan Di SMKS Galang Insan Mandiri - Anda Kelana (ALACRITY : Journal of Education, 2022)
The results of the research on the management of improving the quality of schools/madrasahs conducted at SMKS Galang Insan Mandiri are expected to open insights and find new guidelines for schools in Binjai City in particular and North Sumatra Province in general in an effort to improve the quality of schools/madrasahs through the following steps: -step management; planning, implementation and evaluation based on the quality of national education standards. The existence of public schools, both owned by the government and under the auspices of a foundation that has certain characteristics, is certainly needed by all parties. Maintaining and even improving the quality of schools/madrasahs that have been achieved so far requires careful management handling by making efforts to plan, implement and evaluate continuous, consistent, integrated and comprehensive quality improvement while still being guided by the vision, mission and goals of the school/madrasah that have been established. formulated. All steps of planning, implementation, and evaluation in the three national education standards; content standards, process standards and CAR standards produced in this study are strategic steps to improve the quality of schools/madrasahs. Improving the quality of schools/madrasahs should be carried out in a sustainable manner while prioritizing long-term interests. Schools / Madrasas that have high quality competitiveness can produce quality, competitive and efficient educational outputs.